A Short Review on Green Supply Chain Management Practices: The Impact on Operational and Environmental Performance - Shaikh, F. A.; Shahbaz, M. S.; Odhano, N. (Engineering, Technology & Applied Science Research, 2020)
The aspects of sustainability and ecology have gradually become matters of significant concern within supply chain management processes. The aim of this study is to investigate the impact of the green supply chain on the environment and on operational performance. This study considers environmental management practices within firms, sustainable supply chain management practices relating to suppliers and customers, and environmentally conscious product and process design, by adopting a case-study approach and focusing on four major firms. The findings of this study reveal that the companies applying green supply chain management achieve better environmental performance but at an extra cost. Meanwhile, green practices provide improved customer satisfaction and attraction for retailers, distributors, and authorities.